Teacher Strategies for Digital Religious Literacy Among Generation Alpha Students: Strategi Guru Akidah Akhlak dalam Membimbing Literasi Keagamaan Digital Generasi Alpha - Silva Amanda Putri; Nasrun Salim Siregar (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid advancement of digital technology has fundamentally transformed how students access information, necessitating pedagogical adaptations in religious education. Specific Background: Generation Alpha, characterized by a profound digital native identity, often prioritizes entertainment over educational content and lacks critical verification skills when engaging with digital religious materials. Knowledge Gap: Existing studies have largely examined digital literacy or generational characteristics in isolation, failing to address the specific integration of these factors within Islamic moral education (Akidah Akhlak) frameworks. Aims: This study analyzes the pedagogical strategies employed by Akidah Akhlak teachers at MTs Negeri 2 Deli Serdang to foster digital religious literacy among Generation Alpha. Results: The findings reveal that educators successfully utilize a combination of digital integration, moral internalization, visual media, and dialogic pedagogical methods to cultivate critical thinking and responsible digital ethics. Despite challenges including heterogeneous student digital competencies, time limitations, and inadequate parental supervision these strategies effectively pivot from traditional instruction to a contextually relevant model. Novelty: This research uniquely contributes to the field by proposing a structured integration of Islamic values specifically the tabayyun (verification) principle into digital literacy practices, transforming students from passive consumers into active, ethical participants. Implications: Future educational initiatives should focus on developing collaborative, structured models between schools and parents to ensure the long-term sustainability of digital religious literacy education, thereby safeguarding students against the risks of unchecked digital information. Highlights Guru berhasil mengubah pendidikan moral tradisional menjadi kerangka kerja literasi digital yang adaptif. Integrasi prinsip tabayyun berfungsi sebagai mekanisme inti untuk evaluasi informasi yang kritis. Metode pedagogis aktif dan penggunaan media visual secara signifikan meningkatkan perilaku etis digital siswa. Keywords Teacher Strategy; Moral Creed; Digital Religious Literacy; Generation Alpha; Islamic Education